Chromosomal plasticity and evolutionary potential in the malaria vector Anopheles gambiae sensu stricto: insights from three decades of rare paracentric inversions - Pombi, Marco (BioMed Central, 2008)
BACKGROUND: In the Anopheles gambiae complex, paracentric chromosomal inversions are non-randomly distributed along the complement: 18/31 (58%) of common polymorphic inversions are on chromosome arm 2R, which represents only ~30% of the complement. Moreover, in An. gambiae sensu stricto, 6/7 common polymorphic inversions occur on 2R. Most of these inversions are considered markers of ecological adaptation that increase the fitness of the carriers of alternative karyotypes in contrasting habitats. However, little is known about the evolutionary forces responsible for their origin and subsequent establishment in field populations. RESULTS: Here, we present data on 82 previously undescribed rare chromosomal inversions (RCIs) recorded during extensive field sampling in 16 African countries over a 30 year period, which may shed light on the dynamics of chromosomal plasticity in An. gambiae. We analyzed breakpoint distribution, length, and geographic distribution of RCIs, and compared these measures to those of the common inversions. We found that RCIs, like common inversions, are disproportionately clustered on 2R, which may indicate that this arm is especially prone to breakages. However, contrasting patterns were observed between the geographic distribution of common inversions and RCIs. RCIs were equally frequent across biomes and on both sides of the Great Rift Valley (GRV), whereas common inversions predominated in arid ecological settings and west of the GRV. Moreover, the distribution of RCI lengths followed a random pattern while common inversions were significantly less frequent at shorter lengths. CONCLUSION: Because 17/82 (21%) RCIs were found repeatedly at very low frequencies – at the same sampling location in different years and/or in different sampling locations – we suggest that RCIs are subject mainly to drift under unperturbed ecological conditions. Nevertheless, RCIs may represent an important reservoir of genetic variation for An. gambiae in response to environmental changes, further testifying to the considerable evolutionary potential hidden within this pan-African malaria vector.